A comparative study of blood transfusion process for reducing of wastes and risks in Maharaj Nakhon Si Thammarat Hospital - Narkpetch, Sodsai (Archives of Allied Health Sciences, 2019)
Studying for improving working process to reduce waste and risk in recruiting blood is benefit for safe blood transfusion. To analyze the risk and waste of improving blood donor screening and donor blood processing for reduction of risk and waste at Maharaj Nakhon Si Thammarat Hospital. A retrospective study was performed to analyze for risk and waste in comparison between before and after computer was implemented in mobile blood collection for checking blood donor history since 2017. Recording of blood bag segment number for blood bag verification if necessary was introduced in 2016. Using computer for donor history checking in blood bank and mobile collection reduced the risk and waste of collection blood from previous infected blood donor from 44 units with 24,640 Baht waste in 2015 and 45 units with 25,200 Baht waste in 2016 to 20 units of 11,200 Baht waste in 2017 with statistical significant difference (p-value = 0.018 and 0.0178, respectively). Recording blood bag segment number were able to significantly reduced the waste of blood from 21 and 17 units in 2014 and 2015, respectively to zero waste in 1959 and 1960 and saving of 1.46 % and 1.37% cost (p-value<0.05). Both of computerized blood donor history checking and recording of blood bag segment number enhanced the efficiency of blood transfusion processes by reducing risk and waste.